SHMT2 regulates serine metabolism to promote the progression and immunosuppression of papillary renal cell carcinoma - Kong, Weiyu; Wang, Zhongyuan; Chen, Nuoran; Mei, Yiwen; Li, Yang; Yue, Yulin (Frontiers in Oncology, 2022)
Recent researches had shed light on the wide relationship between tumor metabolism and the tumor microenvironment (TME)1,2. Among them, abnormal serine metabolism represented a momentous component, while its role in papillary renal cell carcinoma (KIRP) remained uncertain. Our study focused on the prognostic value and regulation mechanisms in KIRP. Gene expression profiles and clinical data of KIRP patients were obtained from The Cancer Genome Atlas database (TCGA) and Gene Expression Omnibus (GEO) database. We used Kaplan-Meier curves for survival analysis and consensus clustering for tumor serine metabolic signatures extraction. Functional analysis, including KEGG and gene set enrichment analysis (GSEA), was applied to explore biological characteristics. The gene set variation analysis (GSVA), single-sample GSEA (ssGSEA) and Estimation of Stromal and Immune cells in Malignant Tumor tissues using Expression data (ESTIMATE) methods were utilized to estimate the immune infiltration among subtypes. A total number of 5 serine metabolic genes (SMGs) were chosen to classify KIRP patients. According to the survival-related SMGs, four clusters were determined with diverse prognosis and immune features. Simultaneously, we selected the best and worst clusters (B and D clusters) for further study. Among the two clusters, we discovered great variations in survival, clinical progresssions, oncogenic pathways and TME, which included immune infiltration scores, immunosuppresive cell infiltration and expressions of immune checkpoints. Additionally, we noticed that SMGs, especially SHMT2, exacerbated the carcinogenesis and immunosuppressive cells in KIRP, thus promoting tumor proliferation. Based on our analysis, we elucidated the consistency of higher SHMT2 gene expression as well as higher serine metabolism in tumor cells with worse clinical outcomes in KIRP. SHMT2 might become a novel targeting gene for immunotherapy in KIRP.